Análisis de eficiencia energética de los principales sistemas eléctricos del Hospital General de Latacunga - Chasiluisa Yanchatuña, Sandra Marisol (2022)
In Ecuador, the efficient use of electrical energy has not been prioritized as an objective to achieve a better sustainable development, so that public and private companies do not incorporate an energy saving management plan, one of these public companies is the General Hospital of Latacunga. The present work consists of the analysis of the electrical energy efficiency of the main low-voltage distribution transformers of the Hospital, through the application of an electrical energy audit; using parts of the ISO 50001 standards for the approach of an electrical energy management plan, ISO 50002 as a guide for the procedure of an electrical audit and ARCERNNR 002-20 that dictates the national electrical standards that the electrical system of the hospital must comply with in order to consider that handles a good quality of energy. In order to find an alternative to save electricity and economic.